Determinan Pola Asuh Anak Autisme di Kota Denpasar - Ni Wayan Suarniti; Ni Komang Erny Astiti (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2021)
Children with autism symptoms with late intervention will lead to failure of social development and communication in adulthood. The purpose of writing is to develop instruments related to the determinants of parenting styles for children with autism in Denpasar City. Qualitative research design. The sample is the parents (mother/father) of children with autism at the autism service provider institution in Denpasar City in 2018/2019 who meet the research inclusion criteria. The sampling technique is purposive sampling. Data analysis went through the stages of transcription, reduction, coding, categorization and finding themes. The results of the study are the determinants of parenting styles for children with autism in Denpasar City, including knowledge and perceptions of parents and social support. The conclusion of this study is that knowledge, perception and social support are determinants of parenting patterns for children with autism in Denpasar City. Suggestions for further researchers to carry out mixed methods to clarify research results.